2004
DOI: 10.1260/0309524043729958
|View full text |Cite
|
Sign up to set email alerts
|

On the Rotor Effects upon Nacelle Anemometry for Wind Turbines

Abstract: The objective of this paper is to study the typical atmospheric turbulent flow around the rotor and nacelle of a HAWT, in order to (i) investigate the impact of the turbine's rotating blades on the flow field over the nacelle, i.e. the rotor-nacelle interaction; (ii) assess the appropriate anemometer location on the nacelle, and therefore (iii) establish the relationship between wind speed measured near the nacelle and free stream wind speed. The paper presents a numerical method for investigating the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…Subsequently, some researchers have investigated the applicability of operational nacelle wind data towards inflow research. An obstacle to such research is the modification of nacelle-sampled flow by the turbine structure and rotor circulation, which can cause these measurements to nonlinearly deviate from free-stream values (Antoniou and Pedersen 1997, Smith et al 2002, Smaïli and Masson 2004. Nacelle transfer functions (NTFs), relationships between the nacelle-measured winds and free-stream winds, can be used to prepare nacelle data for use in power output studies, provided that conditions on the data collection platforms are met (Liu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, some researchers have investigated the applicability of operational nacelle wind data towards inflow research. An obstacle to such research is the modification of nacelle-sampled flow by the turbine structure and rotor circulation, which can cause these measurements to nonlinearly deviate from free-stream values (Antoniou and Pedersen 1997, Smith et al 2002, Smaïli and Masson 2004. Nacelle transfer functions (NTFs), relationships between the nacelle-measured winds and free-stream winds, can be used to prepare nacelle data for use in power output studies, provided that conditions on the data collection platforms are met (Liu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that nacelle anemometer measurements can be adjusted by the use of transfer functions between an upwind hub-height measurement and the nacellemounted anemometer measurement (Antoniou and Pedersen, 1997;Hunter et al, 2001, Smith et al, 2002Smaïli and Masson, 2004). The IEC (2013) standard now allows the use of nacelle-mounted anemometers to verify power curves based on these transfer functions, or fitted functions of correction factors between upwind hub-height wind speed (UHWS) measurements and nacelle-mounted anemometer wind speed (NAWS) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, the relationship between UHWS measurements and NAWS measurements has been found to depend on multiple factors, including rotor and turbine control settings such as blade pitch angle and inflow angle, the use of vortex generators, yaw error, terrain, flow induction, calibration of the anemometer, and nacelle height and position (Antoniou and Pedersen, 1997;Dahlberg et al, 1999;Smith et al, 2002;Smaïli and Masson, 2004;Frandsen et al, 2009;Zahle and Sørensen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nacelle‐based observations were originally considered to be too inaccurate for power performance testing since they are influenced by an interference from the nacelle and the moving blades of the wind turbine . Consequently, some studies have looked at numerical modeling of the wind flow around the nacelles to better understand and potentially correct such interferences . Each paper makes some useful recommendations on the treatment of nacelle‐based measurements, including discussions on the location of the anemometers on the nacelle.…”
Section: Introductionmentioning
confidence: 99%
“…14 Consequently, some studies have looked at numerical modeling of the wind flow around the nacelles to better understand and potentially correct such interferences. 12,15 Each paper makes some useful recommendations on the treatment of nacelle-based measurements, including discussions on the location of the anemometers on the nacelle.…”
mentioning
confidence: 99%